1989
DOI: 10.1093/ije/18.2.390
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Domestic Factors on Respiratory Symptoms and FEV1

Abstract: This study was conducted to determine whether indoor air pollution factors affected respiratory function and symptoms in 1357 non-smoking Caucasian children. Interviews were conducted to determine: exposure to pets and to gases, vapours and dusts from hobbies; the use of gas stoves; fireplaces, air conditioners and humidifiers; type of heating systems; and the number of residents, and the number of smokers in the home. The forced expiratory volume in one second (FEV1) was obtained from maximum expiratory flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…In our study gas, coal stoves used for household heating, and ETS were not associated with SLFG. The effect of gas stoves on the respiratory function of children has previously been observed (32). A substantial body of evidence collected from cross-sectional studies showed that ETS may be associated with the lower lung function level in children (33)(34)(35); however, some data refute this statement (36)(37)(38).…”
Section: Discussionmentioning
confidence: 97%
“…In our study gas, coal stoves used for household heating, and ETS were not associated with SLFG. The effect of gas stoves on the respiratory function of children has previously been observed (32). A substantial body of evidence collected from cross-sectional studies showed that ETS may be associated with the lower lung function level in children (33)(34)(35); however, some data refute this statement (36)(37)(38).…”
Section: Discussionmentioning
confidence: 97%
“…Ownership of furry pets has been suggested as a risk factor for wheeze in many clinical studies,8 9 10 11 but epidemiological studies have generally reported no association or an inverse relation to furry pets,2 12 13 14 although a positive association was found in a recent study in Singapore 15…”
Section: Discussionmentioning
confidence: 99%
“…Parental smoking has also been implicated as a risk factor for asthma among young children [6]. Other studies have suggested that heating systems, number of residents, gas cooking and allergens are key factors, which play an important role triggering and exacerbating respiratory illnesses in young children [7][8][9].…”
Section: Introductionmentioning
confidence: 99%